2017
DOI: 10.2134/jeq2016.11.0459
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Effects of Great Cormorant Droppings on Water Quality and Microbial Community of an Artificial Agricultural Reservoir

Abstract: Agricultural reservoirs are established to improve the management of water resources. Waterbirds in protected waters have become a nuisance, however, as nutrients from fecal deposits transported by the waterbirds have served to severely deteriorate water quality. Despite the importance of clean water resources, the microecology of small agricultural reservoirs regularly colonized by transitory waterbirds are seldom reviewed. To improve our understanding of the influence of waterbirds on small bodies of water, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The Curonian Lagoon hosts a large bird community, including tufted ducks and common pochards with 24,500-54,700 and 1,800-41,000 individuals, respectively (Stanevičius et al, 2009), goosanders (Žydelis, 2001), cormorants, with more than 10,000 breading birds (Švažas et al, 2011;Dagys and Zarankaitë, 2013), mallards, geese (3,000-6,500 ind/day) and little and blackheaded gulls (1,000-1,500 ind./day). High densities of water birds are vectors of seeds, invertebrates, bacteria and phytoplankton (Tobiessen and Wheat, 2000), and also contribute to nutrient loads (Manny et al, 1994;Hahn et al, 2007;Green and Elmberg, 2014;Han et al, 2017).…”
Section: Birdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Curonian Lagoon hosts a large bird community, including tufted ducks and common pochards with 24,500-54,700 and 1,800-41,000 individuals, respectively (Stanevičius et al, 2009), goosanders (Žydelis, 2001), cormorants, with more than 10,000 breading birds (Švažas et al, 2011;Dagys and Zarankaitë, 2013), mallards, geese (3,000-6,500 ind/day) and little and blackheaded gulls (1,000-1,500 ind./day). High densities of water birds are vectors of seeds, invertebrates, bacteria and phytoplankton (Tobiessen and Wheat, 2000), and also contribute to nutrient loads (Manny et al, 1994;Hahn et al, 2007;Green and Elmberg, 2014;Han et al, 2017).…”
Section: Birdsmentioning
confidence: 99%
“…In enclosed aquatic ecosystems bird feces may contribute 50-69%, 27-40%, and 70-75% of total C, N, and P loads, respectively (Manny et al, 1994;Post et al, 1998;Boros et al, 2008;Gwiazda et al, 2014). Bird feces have low N:P, implying that water bird excretions may strengthen N limitation and promote cyanobacteria blooms (Rönicke et al, 2008;Han et al, 2017). Birds also have indirect effects on nutrient cycling by removing macrophytes, invertebrates and fish.…”
Section: Birdsmentioning
confidence: 99%
“…Later on, these deposits reach the water with run-off or via groundwater [7]. After microbial degradation residuals from feces are slowly broken down, associated nutrients can be released from the coagulates for periods of 14-21 days [14,44]. Additionally, mineralization processes on settled feces may alter the redox conditions of soils and sediments and favour the chemical release of bound P. All these aspects are important for aquatic ecosystems like the Curonian Lagoon, where large colonies of waterbirds are located along the perimeter of the lagoon and where summer blooms of N-fixing cyanobacteria suggest P excess [19,45].…”
Section: Discussionmentioning
confidence: 99%
“…Bird droppings fertilize the upper layer of the water column and soluble inorganic nutrients may stimulate fast-growing phytoplankton groups [10][11][12]. The organic fraction of feces might also stimulate microbial growth and activity in the water column and on the sediment surface [13,14]. Such nutrient input in some specific areas (e.g., adjacent to nesting or resting places) may represent the dominant input, largely exceeding external sources or nutrient regeneration from sediment [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Roosting species have been shown to contribute to eutrophication of waters below their nest. One study within the closed ecosystem of the Maji Agricultural Reservoir in Wonju, Gangwond-do, South Korea found that cormorants can contribute heavily to the eutrophication of the waters below their roost [14]. In more open waters, such as Lake Balaton in Hungary, bird droppings were still considered to be a potential source of eutrophication, even from only a few hundred nests [15].…”
Section: Introductionmentioning
confidence: 99%